Usage Position and Virtual Keyboard Design Affect Upper-Body Kinematics, Discomfort, and Usability during Prolonged Tablet Typing - Lin, Ming-I Brandon; Hong, Ruei-Hong; Chang, Jer-Hao; Ke, Xin-Min (PloS one, 2015)
The increase in tablet usage allows people to perform computer work in non-traditional office environments. The aim of this study was to assess the effects of changes in tablet keyboard design on postures of the upper extremities and neck, discomfort, and usability under different usage positions during prolonged touch-typing. Eighteen healthy participants familiar with touch-screen devices were randomized into three usage positions (desk, lap, and bed) and completed six, 60-minute typing sessions using three virtual keyboard designs (standard, wide, split). Electrogoniometers continuously measured the postures of the wrists, elbow, and neck. Body discomfort and system usability were evaluated by questionnaires before and immediately after each typing session. Separate linear mixed effects models on various postural measures and subjective ratings are conducted with usage position as the between-subject factors, keyboard design and typing duration as the with-in subject factors were conducted. Using the tablet in bed led to more extended wrists but a more natural elbow flexion than the desk position. The angled split virtual keyboard significantly reduced the extent of wrist ulnar deviation than the keyboard with either standard or wide design. However, little difference was observed across the usage position and keyboard design. When the postural data were compared between the middle and end of typing sessions, the wrists, elbow, and neck all exhibited a substantially increased range of joint movements (13% to 38%). The discomfort rating also increased significantly over time in every upper body region investigated. Additionally, the split keyboard design received a higher usability rating in the bed position, whereas participants had more satisfactory experience while using the wide keyboard in the traditional desk setting. Prolonged use of tablets in non-traditional office environments may result in awkward postures in the upper body that may expose users to greater risks of developing musculoskeletal symptoms. Adequate virtual keyboard designs show the potential to alleviate some postural effects and improve the user experience without changing the tablet form factors.